The Relationship Between Parenting Styles with fine Motor Development in Children Aged 3-5 Years at the Early Childhood Education Center an Nisak, Kediri City - Betristasia Puspitasari (Jurnal EduHealth, 2025)
Children are the nations future generation. Proper parenting can help children achieve optimal growth and development. Child development is a crucial aspect that requires attention at every stage of their development, including fine motor skills. Parenting patterns are one of the factors that contribute to fine motor development in children. The purpose of this research was to determine the relationship between parenting patterns with fine motor development in children aged 3-5 years. The research design used was a correlational study with a cross-sectional approach. The population in this study was all parents with children aged 3-5 years at the Early Childhood Education Center An Nishak in Kediri City, with a total of 24 respondents. In this research, the technique chosen was total sampling. The independent variable in this study was parenting patterns and the dependent variable was the fine motor development of children aged 3-5 years. Data were collected using questionnaires and DDST sheets. The data analysis technique used was Chi-Square. The results of the study showed that the majority of parents who applied a democratic parenting style had children with normal fine motor development results, as many as 16 respondents (76.1%). Based on the results of Chi-Square analysis test with a significance level (α) = 0.05, the Asimp.sig value was 0.04, so it can be concluded that the Asymp.sig value <0.05 so that H1 is accepted, meaning there is a relationship between parenting patterns and fine motor development in children aged 3-5 years. Based on the research results above, it can be concluded that parenting styles significantly influence a child's fine motor development. Therefore, children must be educated with appropriate parenting styles. It is hoped that health workers, especially midwives, will also play a vital role in monitoring children's fine motor development by providing information about age-appropriate fine motor development and appropriate parenting styles to parents.